2021
DOI: 10.1111/jphd.12446
|View full text |Cite
|
Sign up to set email alerts
|

Molar incisor hypomineralization (MIH): prevalence and degree of severity in a Mexican pediatric population living in an endemic fluorosis area

Abstract: Objective: To estimate the prevalence and severity of molar incisor hypomineralization (MIH) in 8 years old children living in an endemic fluorosis area. Methods: MIH prevalence rate was determined from a study sample comprising 613 participants. They were recruited from 11 urban public schools with similar socio-economic status. Oral evaluations were performed and diagnosed MIH teeth were classified under Ghanim et al.'s criteria. Statistical descriptive and comparative analyzes were carried out. Results: Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(102 reference statements)
2
0
0
Order By: Relevance
“…In this study, a supervised machine learning model was constructed by incorporating a variety of factors that impact the occurrence of MIH in endemic fluorosis regions. The nomograms showed that sex had no influence on occurrence, which is consistent with previous studies ( Yi et al, 2021 ; Sosa-Soto et al, 2022 ). Exposure to low-quality shallow underground water did not increase the likelihood of developing MIH.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, a supervised machine learning model was constructed by incorporating a variety of factors that impact the occurrence of MIH in endemic fluorosis regions. The nomograms showed that sex had no influence on occurrence, which is consistent with previous studies ( Yi et al, 2021 ; Sosa-Soto et al, 2022 ). Exposure to low-quality shallow underground water did not increase the likelihood of developing MIH.…”
Section: Discussionsupporting
confidence: 91%
“…Almost all of the included studies reported that molars were more affected than incisors which agrees with the results from other populations [ 35 37 ]. However, variation exists within the included studies according to the most affected dental arch.…”
Section: Discussionsupporting
confidence: 86%